Comprehensive evaluation of clinical, echocardiographic, and CMR findings in dilated cardiomyopathy - Prakash H Chaudhary; Chigullapalli Sridevi; Susheel K. Malani; Digvijay D Nalawade; Ankit Shokeen (Heart India)
Background: Dilated cardiomyopathy (DCM) is a heterogeneous condition with variable prevalence and outcomes worldwide. Accurate diagnosis and risk stratification are critical for optimal management, with advanced imaging playing a key role in assessing myocardial structure and function. Materials and Methods: This cross-sectional study included 75 patients diagnosed with DCM at a tertiary care center between July 2022 and July 2024. Inclusion criteria included patients aged ≥18 years with echocardiographic (ECHO) findings suggestive of DCM. Detailed clinical, ECHO, and cardiac magnetic resonance imaging (CMR) assessments were performed. Fibrosis, left ventricular diastolic dysfunction (LVDD), and other cardiac parameters were evaluated as the potential prognostic factors. Data were analyzed using the Chi-square and Mann–Whitney U-tests for the categorical and continuous variables, respectively. Results: The mean age of the cohort was 52.4 years, with 66.7% being male. Dyspnea (84%) was the predominant symptom, and systemic hypertension (61.3%) and diabetes mellitus (56%) were the most common comorbidities. Echocardiography revealed varying grades of LVDD, with Grade III present in 32%. CMR showed myocardial fibrosis in 17.3% of patients and late gadolinium enhancement in 42.7%. Mortality at 6 months was 20%, with fibrosis (P = 0.044) and advanced LVDD (P = 0.006) significantly associated with poorer outcomes. No single ECHO parameter independently predicted mortality, but trends indicated a higher risk with reduced left ventricular ejection fraction and larger left atrial size. Conclusion: Fibrosis and advanced LVDD are the significant predictors of mortality in DCM, underscoring the importance of comprehensive imaging for the prognosis. Future studies should explore targeted interventions to improve the outcomes in high-risk subgroups.